Dynamic Alterations of Gut Microbiota in Porcine Circovirus Type 3-Infected Piglets - Hou, Lei; Wang, Jing; Zhang, Wei; Quan, Rong; Wang, Dan; Zhu, Shanshan; Jiang, Haijun; Wei, Li; Liu, Jue (Frontiers in Microbiology, 2020)
Porcine circovirus type 3 (PCV3) is a novel porcine circovirus species associated with several diseases such as porcine dermatitis and nephropathy syndrome (PDNS)-like clinical signs, reproductive failure, cardiac pathologies, and multisystemic inflammation in piglets and sows. Currently, many studies have focused on the interaction between microbiota composition and disease progression. However, dynamic changes in the composition of the gut microbiota following PCV3 infection are still unknown. In this study, alterations in gut microbiota in PCV3-inoculated and sham-inoculated piglets were analyzed at various time points [7, 14, 21, and 28 days post-inoculation (dpi)] using the Illumina MiSeq platform. Using principal coordinate analysis, obvious structural segregations were observed in bacterial diversity and richness between PCV3- and sham-inoculated piglets, as well as at the four different time points. The abundance of gut microbiota exhibited a remarkable time-related decrease in Clostridium_sensu_stricto_1 in PCV3-inoculated piglets. In addition, significant differences were observed in functional classification based on cluster of orthologous groups assignment, between PCV3- and sham-inoculated piglets. Our findings demonstrated that PCV3 infection caused dynamic changes in the gut microbiota community. Therefore, regulating gut microbiota community may be an effective approach for preventing PCV3 infection.